RELATIONSHIP BETWEEN DIET AND STRESS WITH A HISTORY OF GASTRITIS IN ADOLESCENTS AT MADRASAH ALIYAH NEGERI 2 CIPONDOH TANGERANG CITY IN 2023 - Nurmalia Lusida; Nurnida Ashofa; Andriyani; Dina Rahma Fadlilah; Dadang Herdiansyah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Gastritis is known among people as stomach ulcers or heartburn that comes suddenly. In developing countries, the incidence of gastritis mostly occurs in the young age group and is dominated by ≤ 20 years, namely 78.6% of this age is a teenager caused by internal factors, namely conditions that can trigger excessive gastric acid secretion and external factors that cause irritation and infection. The purpose of this study was to see if there was a relationship between eating frequency, type of meal, portion size, and stress with a history of gastritis. This study used the Quantitative Analytic method with a cross-sectional study design. This research was conducted in October-December at Madrasan Aliyah Negeri 2 Cipondoh, Tangerang City. The population of this research is all students of MAN 2 Cipondoh, the target population is students of grades 11-12 of MAN 2 Cipondoh. The sample size of this study was 93 students of Cipondoh 2 Madrasah Aliyah. While taking samples using the Simple Random Sampling technique. Analysis of the research data is using chi-square. Based on the analysis, it was found that all independent variables were related to the dependent variable. Includes, frequency of eating with a p-value of 0.000, types of eating with a p-value of 0.000, portions of food with a p-value of 0.034, and stress with 0.000. It is hoped that the students of MAN 2 Cipondoh will pay more attention to their diet considering that almost half of the respondents have less frequency of eating, consume irritating types of food, and have fewer food portions.